2019
DOI: 10.1002/er.4585
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of thermal performance of geometrically modified spherical ice capsules during the discharging period

Abstract: Summary Ice thermal energy storage (ITES) is a significant option for shifting cooling load from peak hours to off‐peak hours in order to reduce the cooling cost and equipment capacity. Encapsulated ITES system is one of the most preferred types of ITES systems, because it is easier to apply and has lower initial cost than other types of ITES systems. Capsule geometries have great impact on the thermal performance of the encapsulated ITES system. Spherical capsules are widely used in the application because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Erdemir 10 computationally analyzed and compared various geometric adjusted spherical capsules with regular ones. Their results demonstrated that the geometrically adjusted capsules had greater performance compared to the regular ones.…”
Section: Introductionmentioning
confidence: 99%
“…Erdemir 10 computationally analyzed and compared various geometric adjusted spherical capsules with regular ones. Their results demonstrated that the geometrically adjusted capsules had greater performance compared to the regular ones.…”
Section: Introductionmentioning
confidence: 99%